ОРИЕНТАЛИЗМ В ПУШКИНСКОМ ЦИКЛЕ «ПОДРАЖАНИЯ КОРАНУ» (Scientific journal of the Fergana State University, 2023)
In this article the author reveals the problem of  the origin and significance of Orientalism in Russian literature, the connection between East and West. Analyzing Pushkin's "Imitations of the Koran", the author made linguistic conclusions concerning word formation, linguistics and loan-words.